Effectiveness of Tofacitinib in Pre-adolescent Alopecia Areata: A Retrospective Case Series and Literature Review - Jundong Huang; Tingting Li; Zixin Tan; Yan Tang; Ji Li; Fenfang Liu; Wei Shi (Medical Journals Sweden, 2023)
Alopecia areata (AA) is a common cause of hair loss in children. Despite numerous therapeutic options for paediatric AA, none have been found to be both effective and safe. Recent studies have demonstrated the efficacy and safety of the Janus kinase (JAK) inhibitor tofacitinib in adult patients with AA, whereas data on paediatric patients with AA in real-world practice are limited. This was a single-centre, retrospective study that included 11 pre-adolescent patients with AA treated with tofacitinib between December 2021 and September 2022. Clinical characteristics of patients, clinical response and adverse events were evaluated. Overall, 82% (9/11) of patients experienced hair regrowth and 64% (7/11) of patients experienced over 50% improvement in their Severity of Alopecia Tool (SALT) scores. Adverse events were mild. In the literature, tofacitinib has been used to treat AA in 31 children ≤12 years of age who failed to respond to prior treatments. Eighty-seven percent (27/31) of these patients showed significant responses based on changes in their SALT scores. This case series demonstrates that oral tofacitinib is an effective and safe treatment option for paediatric AA, particularly for children who have failed to respond to traditional treatments or are not suitable for such treatments.